Journalists and mental health: The psychological toll of covering everyday trauma. (June 2019) - Seely, Natalee
Journalists are often first responders and eyewitnesses to violent news events. Trauma reporting can take its toll, resulting in mental health effects. Addressing the solution requires understanding the problem. This multimethod study used a national survey of journalists (N = 254) that shows that as trauma coverage frequency and intensity increase, so does the severity of post-traumatic stress disorder symptoms. In-depth interviews offer personal narratives of effects from traumatic reporting. Common coping mechanisms include disconnecting from work in various ways, purging emotions, talking about trauma, and remembering their jobs' higher purposes. Suggestions include humanizing the newsroom and teaching about trauma reporting.